Morphological and palynological assessment of taxonomically problematic genus Paspalum based on light and scanning electron microscopy. Issue 2 (16th September 2021) - Shaheen, Shabnum; Khan, Muhammad Asaf; Shahid, Muhammad Naveed; Shamim, Zeeshan; Rasool, Bilal; Hussain, Khadim; Khalid, Sana; Harun, Nidaa; Siddique, Riffat; Sonia, Romaisha; Khan, Farah
Abstract: Present research work was carried out to clarify the variations among species of genus Paspalum morphologically and palynologically as this genus is taxonomically difficult due to having multiple similar morphologically overlapping characters which make it difficult to identify. Henceforth present research work was carried out to delimit taxa within the same genus by morphological and palynological tools through light microscopy (LM) and scanning electron microscopy (SEM). Both these tools are considered as the most useful taxonomic characters for taxonomically problematic genera. The results showed a lot of variations among morphological characters. In Paspalum dilatatum, the upper glume was ovate whereas in the other two species, the upper glume was elliptic. The upper glume apex found in P. dilatatum and Paspalum scrobiculatum was obtuse whereas in Paspalum distichum, upper glume apex was acute. Glume nerves showed variation in all three species. Paspalum distichum was 3 nerved, P. scrobiculatum was 5–7 nerved, and P. dilatatum was 5–9 nerved. All three species showed variation in lemma nerves. Paspalum scrobiculatum had 3 nerved lemma whereas in P. distichum 3–5 nerved and P. dilatatum 5–9 nerved lemma were present. In polar and equatorial view, pollen grains ranged from 25 (20–30) to 37.5 (30–45) μm. Paspalum distichum appeared to be the smallest in size whereas P. dilatatum was the largest. Exine thickness ranged from 0.75 (0.5–1) to 1.35 (1.2–1.5) μm. The higher value of pollen fertility was found in P. scrobiculatum as 87.69% and the lowest value was in P. distichum as 78.08%. Morphological keys were also given for correct identification. Abstract : Grasses face the problems in their identification due to confusion in nomenclature, taxonomic ranking, and differentiation of various species at specific level and sometimes at generic level also. Among these difficult taxa, one is the genus Paspalum which is considered as a taxonomically difficult genus due to its similar overlapping morphological characters. Therefore, the morphological and palynological studies of this genus were carried out to study variations and to delimit its different taxa. This is the first study in Pakistan in which both these parameters were used in combination to identify and distinguish taxa not only through LM but also through SEM. The morphological results showed a lot of variations within the studied species. Palynological characteristics were also proved a useful taxonomic tool for difficult grass taxa. The results of this study conclude that morphological as well as the palynological characters are helpful in identification and delimitation of taxa and genera into tribes and subfamilies.